Want this question answered?
Be notified when an answer is posted
The nth term of an arithmetic sequence = a + [(n - 1) X d]
7 - 4n where n denotes the nth term and n starting with 0
The nth term is 3(n+1). The twenty-third term is equal to 3 x (23 + 1) = 72
xn=x1+(n-1)v^t and Pn=P1+(n-1)iP1
The nth term of a arithmetic sequence is given by: a{n} = a{1} + (n - 1)d → a{5} = a{1} + (5 - 1) × 3 → a{5} = 4 + 4 × 3 = 16.
The nth term of an arithmetic sequence = a + [(n - 1) X d]
The nth term in this arithmetic sequence is an=26+(n-1)(-8).
The difference between successive terms in an arithmetic sequence is a constant. Denote this by r. Suppose the first term is a. Then the nth term, of the sequence is given by t(n) = (a-r) + n*r or a + (n-1)*r
The nth term is -7n+29 and so the next term will be -6
The given sequence is an arithmetic sequence with a common difference of 1. The nth term of an arithmetic sequence can be found using the formula: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term in the sequence, and d is the common difference. In this case, the first term (a_1) is 4 and the common difference (d) is 1. Therefore, the nth term for this sequence is a_n = 4 + (n-1)(1) = 3 + n.
The given sequence is an arithmetic sequence with a common difference that increases by 1 with each term. To find the nth term of an arithmetic sequence, you can use the formula: nth term = a + (n-1)d, where a is the first term, n is the term number, and d is the common difference. In this case, the first term (a) is 3 and the common difference (d) is increasing by 1, so the nth term would be 3 + (n-1)(n-1) = n^2 + 2.
The given sequence is an arithmetic sequence with a common difference of 6. To find the nth term of this sequence, we can use the following formula: nth term = first term + (n - 1) x common difference where n is the position of the term we want to find. In this sequence, the first term is 1 and the common difference is 6. Substituting these values into the formula, we get: nth term = 1 + (n - 1) x 6 nth term = 1 + 6n - 6 nth term = 6n - 5 Therefore, the nth term of the sequence 1, 7, 13, 19 is given by the formula 6n - 5.
The given sequence is an arithmetic sequence with a common difference of 4 between each term. To find the nth term of an arithmetic sequence, we use the formula: nth term = a + (n-1)d, where a is the first term, d is the common difference, and n is the term number. In this case, the first term (a) is -3, the common difference (d) is 4, and the term number (n) is the position in the sequence. So, the nth term of the given sequence is -3 + (n-1)4 = 4n - 7.
The nth term is referring to any term in the arithmetic sequence. You would figure out the formula an = a1+(n-1)d-10where an is your y-value, a1 is your first term in a number sequence (your x-value), n is the term you're trying to find, and d is the amount you're increasing by.
The nth term for that arithmetic progression is 4n-1. Therefore the next term (the fifth) in the sequence would be (4x5)-1 = 19.
tn = a + (n - 1)d where a is the first term and d is the difference between each term.
7 - 4n where n denotes the nth term and n starting with 0